Same incidence of adverse drug events after codeine administration irrespective of the genetically determined differences in morphine formation. - Eckhardt, K; Li, S; Ammon, S; Schänzle, G; Mikus, G; Eichelbaum, M (PAIN, 1998)
The analgesic effect and adverse events of the weak opioid codeine is assumed to be mediated by its metabolite morphine. The cytochrome P-450 enzyme CYP2D6 catalysing the formation of morphine exhibits a genetic polymorphism. Two distinct phenotypes, the extensive (EMs) and poor metabolisers (PMs), are present in the population. The prevalence of PMs in the Caucasian population is 7% to 10%. Since PMs do not express functional CYP2D6, they have a severely impaired capacity to metabolise drugs which are substrates of this enzyme. Provided the analgesic effect and the adverse events of codeine are mediated by its metabolite morphine, large phenotype-related differences are to be expected and PMs, as they form only trace amounts of morphine, can serve as a model to test the hypothesis whether the analgesia and adverse events of codeine are mediated by the parent drug or its metabolite morphine. Therefore we have studied in a randomised placebo-controlled double-blind trial the analgesic effect of 170 mg codeine (p.o.) compared to 20 mg morphine (p.o.) and placebo in 9 EMs and 9 PMs using the cold pressor test. The duration and intensity of the side effects were assessed using visual analogue scales (VAS). Codeine and morphine concentrations were measured in serum and urine. Compared to placebo, 20 mg morphine caused a significant increase in pain tolerance in both phenotypes, EMs and PMs (16.2+/-27.4 vs. -0.66+/-27.4 s x h, n=18). However, following administration of codeine, analgesia was only observed in EMs but not in PMs (EMs: 54.9+/-42.2 vs. 1.7+/-4.2 s x h, P < 0.01; PMs: 9.6+/-10.9 vs. 3.3+/-23.7 s x h, not significant). Adverse events were significantly more pronounced after morphine and codeine compared to placebo in both EMs and PMs. In contrast to the phenotype-related differences in the analgesic effect of codeine, however, no difference in adverse events between the phenotypes could be observed. In the pharmacokinetic studies, significant differences between the two phenotypes in the formation of morphine after codeine administration could be observed. Whereas morphine plasma concentrations were similar in PMs (Cmax: 44+/-13 nmol/l: AUC: 199+/-45 nmol x h/l) and EMs (Cmax: 48+/-17 nmol/l); AUC: 210+/-65 nmol x h/l) after morphine administration, following 170 mg codeine, morphine plasma concentrations comparable to those after morphine application were only observed in EMs (Cmax: 38+/-16 nmol/l; AUC: 173+/-90 nmol x h/l). In PMs only traces of morphine could be detected in plasma (Cmax: 2+/-1 nmol/l; AUC: 10+/-7 nmol x h/l). The percentage of the codeine dose converted to morphine and its metabolites was 3.9% in EMs and 0.17% in PMs. The interindividual variability in analgesia of codeine which is related to genetically determined differences in the formation of morphine clearly indicate that this metabolite is responsible for the analgesic effect of codeine. In contrast to the analgesic effect, frequency and intensity of the adverse events did not present significant differences between the two phenotypes. These findings have implications for the clinical use of codeine. Since side effects occurred in both EM and PM subjects, the use of codeine as an analgesic will expose 7% to 10% of patients who are PMs to the side effects of the drug without providing any beneficial analgesic effects.